Rancang Bangun Peminjaman Buku pada Perpustakaan STMIK Kaputama Menggunakan RFID Berbasis IoT - Assya Harnita Lubis; Husnul Khair; Muammar Khadapi (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The rapid advancement of information technology has brought significant transformation across multiple sectors, including library management systems. One of the pressing needs in higher education libraries is the development of an efficient, accurate, and secure borrowing system that reduces human error and improves service quality. This study aims to design and implement a book borrowing system for the STMIK Kaputama library by utilizing Radio Frequency Identification (RFID) technology integrated with the Internet of Things (IoT). The proposed system employs the ESP32 microcontroller as the core controller, supported by the RFID RC522 module and buzzer as primary devices to facilitate the automatic identification of library members and borrowed books. The borrowing and returning process is executed through RFID card scanning, with all transaction data transmitted via WiFi and stored in a MySQL database, which is managed through a PHP-based web platform. The development process follows the Agile methodology, enabling iterative improvement and adaptability to user requirements. System testing demonstrates that the integration of RFID and IoT technology significantly enhances the efficiency, accuracy, and speed of library operations compared to the previous manual system. Furthermore, the system allows real-time recording of borrowing transactions, monitoring of user activities, and centralized data management. These features not only streamline library services but also improve data security and reduce the risk of loss or duplication of records. Overall, the implementation of this RFID-IoT-based system provides an innovative solution for modernizing library management, particularly in higher education institutions. The system ensures faster services, minimizes errors, and creates a structured and reliable digital infrastructure to support academic information services. This study highlights the potential of combining RFID and IoT technologies to improve the quality and effectiveness of library systems in the digital era.